The role of terminological dictionaries in learning foreign languages by students of technical colleges - Zubenko, K. V.; Зубенко, K. В. (Center of modern pedagogy «Learning without Frontiers», 2017)
The article analyzes theoretical bases and experience of developing learner’s terminological dictionaries. The article points out that the process of formation of terminological dictionaries for students, especially at technical educational institutions, is marked by the following contradictions: inaccuracy during the selection of included terms, the variability of the translation and insufficient terms description, insufficient number of examples for the use of terms in the appropriate context, low language skills of students. The morphological structure of terms was considered. The role of context in the compiling of terminological dictionary was identified. The article highlights the main methods of terms translation.

У статті аналізуються теоретичні основи і досвід складання термінологічних словників для студентів технічних вузів. У роботі наголошується, що процес формування термінологічних словників для студентів, особливо в технічних навчальних закладах, характеризується наступними протиріччями: неточність під час вибору включених термінів, варіативність перекладу і недостатній опис термінів, недостатня кількість прикладів для використання термінів у відповідному контексті, низькі мовні навички студентів. Стаття розглядає морфологічну структуру термінів та визначає роль контексту в складанні термінологічного словника. Висвітлено основні методи перекладу термінів.
Роль термінологічних словників у вивченні іноземних мов у технічних ВНЗ
Keywords: terminology; term; dictionary; technical; students; термінологія; термін; словник; технічний; студенти